Parental Perceptions of STEAM Education of Early Childhood Education for Social Development:A Case of St. Joseph Kindergarten Asmara Eritrea - Elias, Samson Kifletsion; Stonier, Francis; Musengamana, Irene (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
In the twenty-first century, parents face the most intense competition in raising gifted kids with high STEAM (Science, Technology, Engineering, Art, and Mathematics) quality who are prepared to take on difficulties, and kindergarten is the foundation for this holistic life of the child. However, there can be no meaningful social development without parental involvement in the child's STEAM education. The current study examines how parents view STEAM education for young children in Asmara, Eritrea's St. Joseph STEAM-integrated kindergarten to ensure healthy social development. The study used mixed techniques to identify parents' perspectives toward STEAM education and how it affects their kindergarteners' academic and social/emotional growth. It also investigated the barriers that prevent parents from becoming involved in their children's education. The quantitative data was gathered from thirty parents (n=30). On the other hand, semi-structured interviews with fifteen parents involved them. The results showed that in the kindergarten used in the case study, parents were seen as being involved at home and paying for the child's transportation and school expenses. Furthermore, it was discovered that parents encourage their kids' social and emotional growth. In addition, the study discovered a few characteristics that influence parents' perceptions of STEAM education in kindergarten, including a lack of STEAM education knowledge and awareness, a lack of time for a child's follow-up, low parental income, low educational attainment, and a lack of someone to watch the other kids. Furthermore, the current study recommends further research that incorporates various types of kindergartens with different parents to enrich the data on parental perception of STEAM education in Eritrea.